2015
DOI: 10.17503/agrivita-2015-37-1-p075-088
|View full text |Cite
|
Sign up to set email alerts
|

POD NUMBER AND PHOTOSYNTHESIS AS PHYSIOLOGICAL SELECTION CRITERIA IN SOYBEAN (Glycine max L. Merrill) BREEDING FOR HIGH YIELD

Abstract: Field studies were conducted in two years using 638 F2 and 1185 F3 lines of selected 16 F1 and 15 F2 parent lines (80 pods plant . The ratio of pod number per plant and Pmax varied between lines and were used to group lines resulting in close relationships between Pmax and pod number. It is concluded that the use of pod number and CER (Pmax) as selection criteria offers an alternative approach in soybean breeding for high yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Yield loss, expressed as yield proportion of control plant yield due to varying levels of exposure to dicamba in irrigation water, was projected based on models available in the literature using 14 DAT for plant injury assessments (Egan et al 2014a) and pod counts (Sitompul et al 2015). These estimates were then related to estimates of dicamba dose (mg cm −2 ) delivered at each dicamba concentration to the surface area of the potted field soil, which was subsequently scaled up to approximate field rates (g ha −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield loss, expressed as yield proportion of control plant yield due to varying levels of exposure to dicamba in irrigation water, was projected based on models available in the literature using 14 DAT for plant injury assessments (Egan et al 2014a) and pod counts (Sitompul et al 2015). These estimates were then related to estimates of dicamba dose (mg cm −2 ) delivered at each dicamba concentration to the surface area of the potted field soil, which was subsequently scaled up to approximate field rates (g ha −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Projected yield proportions estimated from percent plant injury (Egan et al 2014a) and from pod counts (Sitompul et al 2015) ranged from 1 to 0.63 and 0.95 to 0, respectively (Figure 3). For both sets of projections, yield proportion decreased with increasing dicamba dose above 6.2 g ha −1 (dose equivalent to the 0.1 mg L −1 treatment).…”
mentioning
confidence: 99%
“…According to Oz et al (2009), and Valencia-Ramirez and Ligarreto-Moreno (2012) number of pods and number of nodes gave direct positive effect to seed weight per plant. Malik et al (2007) and Sitompul et al (2015) suggested that number of pods may be used as one of selection criteria in soybean breeding for high yield. Additionally, the highest yield per plant in this study was found on genotypes with large and medium seed size.…”
Section: Resultsmentioning
confidence: 99%